2018
DOI: 10.1080/21501203.2018.1492981
|View full text |Cite|
|
Sign up to set email alerts
|

Regulatory network of genes associated with stimuli sensing, signal transduction and physiological transformation of appressorium inMagnaporthe oryzae

Abstract: Rice blast caused by Magnaporthe oryzae is the most destructive disease affecting the rice production (Oryza sativa), with an average global loss of 10–30% per annum. Recent reports have indicated that the fungus also inflicts blast disease on wheat (Triticum aestivum) posing a serious threat to the wheat production. Due to its easily detected infectious process and manoeuvrable genetic manipulation, M. oryzae is considered a model organism for exploring the molecular mechanism underlying fungal pathogenicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 118 publications
(105 reference statements)
0
23
0
Order By: Relevance
“…G-protein/cAMP signaling is required for appressorium formation and pathogenicity in the rice blast fungus M . oryzae [ 28 , 62 , 63 ]. The regulators of G-protein signaling, in particular MoRgs1, also plays an important role in these function [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…G-protein/cAMP signaling is required for appressorium formation and pathogenicity in the rice blast fungus M . oryzae [ 28 , 62 , 63 ]. The regulators of G-protein signaling, in particular MoRgs1, also plays an important role in these function [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…3(A)). Since hydrophobins mediate the proper and timely sensing of the host surface cues, 37 we speculated that sanguinarine may target the fungal hydrophobins and impair germ tube development. To test this, we quantified the expression profiles of four hydrophobin encoding genes by qRT‐PCR and found that a crucial fungal hydrophobin MoMPG1 is dramatically reduced by ≥95% change while MoMHP1 , MGG_09134 and MGG_10105 are up‐regulated by several fold in sanguinarine‐treated strains (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Genomics and their interconnected disciplines have provided a fertile platform to address most of these issues and controversies related to the formation and functioning of appressoria. Genomic data and novel techniques have contributed towards a better understanding of these fungal-host interactions from appressorium formation to host invasion [28][29][30][31][32]. Advances in reverse genetic techniques have enabled cloning of diverse genes predicted to be involved in these interactions, and many are characterized via various functional genomic approaches [17,21,28,[33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%